Reliability of Slice-Encoding for Metal Artifact Correction (SEMAC) MRI to Identify Prosthesis Loosening in Patients with Painful Knee Arthroplasty: A Prospective, Single-Center, Surgical Validation Study - Takahashi, Tsuneari; Thaker, Siddharth; Lettieri, Giovanni; Redmond, Anthony; Backhouse, Michael R.; Stone, Martin; O'Connor, Philip J.; Pandit, Hemant (Indian Journal of Radiology and Imaging, 2025)
To validate reliability of slice-encoding for metal artifact correction (SEMAC) sequences in identifying prosthesis loosening in patients with painful knee arthroplasties (KAs) by comparing SEMAC-magnetic resonance imaging (MRI) findings to surgical outcomes—the gold standard.We prospectively followed 44 painful KA patients with possible aseptic prosthesis loosening at our tertiary care institution from 2011 to 2017. Potential cases of infective loosening were excluded making ours a selective study population. We acquired conventional and SEMAC-MRI images for all patients on 1.5-T MRI scanner. Two consultants scored MRI findings for complications such as osteolysis and bone marrow edema systematically. Scoring variations were settled by consensus. We used the Mann–Whitney U test and Wilcoxon signed-rank test for quantitative analysis and Spearman's rank-order correlation for correlation analysis of SEMAC findings and surgical outcomes, and followed the Outcome Measurements in Rheumatology filter methodology to assess the ability of SEMAC-MRI to detect prosthetic loosening.Eleven patients needed revision surgery—seven had prosthesis loosening and four had retained native compartment osteoarthritis. Thirty-three were treated conservatively, of which 17 had spontaneous pain resolution and 8 had extra-articular causes—referred pain from hip (1 patient) and lumbar (7 patients) degeneration. Eight patients had adequate pain control without prosthesis loosening on follow-up. T1W-SEMAC identified surgically proven prosthesis loosening in all cases and short tau inversion recovery (STIR)-SEMAC diagnosed bone marrow edema (BME) in all our true positive cases. Sensitivity, specificity, positive predictive value, and negative predictive value of SEMAC-MRI for component loosening compared with gold standard were 100, 97.0, 88.9, and 100% in T1W-SEMAC, 75.0, 45.5, 25.0, and 88.2% in STIR-SEMAC, and 75.0, 93.9, 75.0, and 93.9% in proton density-weighted-SEMAC.SEMAC-MRI can accurately detect surgically verifiable prosthesis loosening and differentiate nonspecific BME from prosthesis loosening.
Keywords: knee arthroplasty; MRI; artifact reduction; SEMAC; revision surgery